Media environment of 2020: modeling of the event as a precession of this event (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article deals with the contravention of basic principles of journalistic activity (balance and impartiality of information feed), emphasizes the need of keeping professional and ethical standards by the media representatives. There are analyzed texts discriminatory ideas that contain with verbal aggression, promote intolerance, impose confrontation, exploit an idea of “Your closest circle”. The author defends the requirement of reliability of the information, its unbiased presentation, the morality of the journalist's reasoning. Emphasis is placed on the need of the media to be responsible for studying its audience, solving the problem of information hygiene. The media environment of 2020 demonstratively shows the manipulation of information. We observe the modeling of the event as a precession of this event. The formation of “journalism of screenshot” is rising nowadays, the basis for creating messages is information obtained on social networks, blogs, comments, etc. The audience for which it is intended is at the same time its creator, such a collective author is not responsible for the dissemination of false information, and its verification is very often neglected. Despite their information poverty, unverified facts, the anonymity of materials, such messages are qualified to be threatening: they trouble the public, change, distort the information picture of the world. The appearance among the news of a large number of short materials, designed for a cursory perception, contributes to the growth and acceleration of information flows, which is one of the main trends in the media sphere.
Keywords: media environment; manipulation; modeling of the event; reliability of information; information picture of the world